Implementasi Pendidikan Karakter dalam Pembentukan Taruna Pelayaran - Trisnowati Rahayu; Eddi Eddi; Teguh Pribadi; Maulidiah Rahmawati (Journal on Education, 2024)
Character education has its own uniqueness when applied in the context of shipping cadet education. Sailing cadets are those who are undergoing education to become reliable sailors or sailors. In this profession, it requires not only technical expertise in navigation and ship operations, but also a strong character to face challenges in an often harsh and dangerous maritime environment. Qualitative method with case study is a suitable research approach to investigate the implementation of character education in the formation of shipping cadets. Through this method, research will be conducted in depth to understand how character education is integrated in curriculum and daily practice in specific shipping schools. In this context, research shows that there is a need to strengthen the integration of character education in the cruise education curriculum to ensure that character values and principles are not only taught separately, but also integrated in every aspect of cadet learning and experience. This can be done through the development of more holistic and well-rounded programs, as well as through training for cruise school faculty and staff to understand how to best integrate character education into their teaching. Studies show that cadets consider strong character important in the maritime profession. However, there are variations in their views on the effectiveness of character education in cruise schools. There needs to be stronger integration between character education and technical curriculum, as well as training for shipping school teachers and staff. The findings of this study provide the basis for the development of more effective strategies in improving the integration of character education in cruise schools.